The Power of Protein - Katt, Megan (My University, 2025)
Protein intake plays a crucial role in the overall health and well-being of cancer patients, supporting muscle maintenance, immune function, treatment tolerance, and recovery. Adequate protein consumption is particularly important for individuals undergoing cancer treatment, as they often experience increased protein and energy needs due to the effects of the disease and its therapies. Research has shown that higher protein intake can help preserve lean body mass, promote wound healing, and enhance the body's ability to withstand treatment-related side effects (Baracos et al., 2018). One of the challenges cancer patients face is meeting their protein requirements, especially when experiencing side effects such as reduced appetite, taste changes, or gastrointestinal distress. Studies indicate that many oncology patients fail to consume enough protein to support optimal health during treatment, which can contribute to muscle loss, fatigue, and decreased treatment tolerance (Bauer et al., 2011). While cancer cachexia—a syndrome characterized by muscle wasting and weight loss—is a concern for some patients, the benefits of protein intake extend to all individuals with cancer, regardless of their specific diagnosis or nutritional status (Arends et al., 2017). A high-protein diet, combined with targeted nutritional support, has been shown to improve clinical outcomes by reducing the risk of malnutrition and enhancing overall recovery (Weimann et al., 2017). Given the essential role of protein in healing and resilience, integrating protein-focused nutrition strategies into cancer care can support patients in maintaining strength, improving quality of life, and optimizing their response to treatment. The initiative consisted of weekly sessions, each dedicated to a specific aspect of protein’s role in cancer care: (1) muscle maintenance and cachexia, (2) immune function, (3) wound healing, and (4) nutritional support for treatment tolerance and recovery. Learning objectives for participants included understanding the importance of protein in cancer treatment, identifying protein-rich food sources, and implementing strategies to increase protein intake despite treatment-related challenges. The program was delivered through multiple educational formats, including dietitian-led presentations, informational handouts, interactive educational booths, and recipe demonstrations. Key resources developed for the initiative included a Protein Food and Drink Handout, a Dietitian Info Card, and a Power of Protein presentation, which collectively provided practical dietary recommendations tailored to cancer patients’ nutritional needs. Research supports that providing clear, visually engaging educational materials can improve dietary adherence and patient outcomes (Bauer et al., 2011). Additionally, an educational booth was set up at the Tammy Walker Cancer Center to engage both patients and healthcare providers, increasing awareness of the importance of protein in oncology nutrition. The initiative also incorporated recipe demonstrations and food sampling to encourage patients to incorporate high-protein foods into their diets, acknowledging the common barriers of fatigue and lack of appetite that can impede proper nutrition (Mann et al., 2013). Registered dietitians (RDs) play a crucial role in addressing the nutritional challenges faced by cancer patients. Studies indicate that individualized nutrition care from RDs can improve patient outcomes by managing treatment side effects, reducing hospitalizations, and enhancing quality of life (Weimann et al., 2017). By integrating nutrition education into oncology care, The Power of Protein initiative sought to bridge the gap between dietary recommendations and practical application, ultimately empowering patients with the knowledge and tools to meet their increased protein needs during cancer treatment.
Keywords: Protein; Cancer; Muscle; Nutrition; Tolerance; Recovery